PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN DAN SUBSEKTOR FARMASI DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Ronald Hasudungan Rajagukguk; Mas Intan Purba; Marvina Marvina; Jenny Yanto; Stephanie Stephanie (Jurnal Akrab Juara, 2019)
The cause of business competition is tight, because there are many competing companies that have good competitive quality. One of them is the food and beverage subsector and the pharmaceutical subsector. The phenomenon that occurs in the company is an increase in the debt to equity ratio, return on equity and investment decisions. The problems of the research are formulated as follows: whether there is an influence of the debt to equity ratio, return on equity and investment decisions on the value of the company in the food and beverage subsector and the pharmaceutical subsector which is listed on the Indonesia Stock Exchange in the period 2013-2017. The research method used is a quantitative research method with a type of descriptive research and the nature of research is casual research. Documentation is used to collect data. Multiple linear regression analysis is a method of data analysis, coefficient of determination, F test and T test. Purposive sampling technique is a sampling technique with certain criteria there are 17 companies as research samples. Based on the results of this study indicate that the debt to equity ratio, return on equity and investment decisions simultaneously have a significant effect on firm value with a Sig = 0,000. Partially, debt to equity ratio, return on equity and investment decisions have a significant effect on firm value with a Sig = 0,000 value